Construção e avaliação de sistema de segunda opinião médica em radiologia - Neira, Ricardo Alfredo Quintano [UNIFESP] (2009)
INTRODUCTION. The second opinion can be defined as the search of advices or medical information between health professionals. OBJECTIVE. The objective of this work is to present the steps of the construction of a second opinion system, as well as the evaluation results of the developed system. METHODS. In this work an observational study with an empirical ethnographic research focus was implemented. A web system was developed based on open-source technologies. For the evaluation, the system was used by 49 residents from the Federal University of São Paulo that informed their opinion to 52 medical second opinion requests. Questionnaires of previous knowledge, request, opinion and satisfaction where employed as evaluation tools. RESULTS. 1.891 second opinion responses were given by the physicians to the 52 requests. Regarding to the user satisfaction evaluation, the system presents a 87,8% mean in the easy utilization item and a 95,6% mean in learning to operate the system. The physicians showed the necessity to add resources to help observing images, as example, magnifying, brightness and contrast, on 38,2% of the responses. 47,3% responses indicated also that clinical information is the most important information for a second opinion emission. Inappropriate language was found on responses for medical second opinion requests which could difficult physicians’ cooperation. CONCLUSION. The results of the development and evaluation of the second opinion system show that the defined process was effective for the achievement of remote radiology second opinion.